Digitalization of management processes in scientific and educational organizations - Andrey Ronzhin; Milos Zelezny (Управленческое консультирование)
Document circulation and communication between organizations, their structural subdivisions and employees are increasingly being made on the basis of infocommunication technologies and paperless digital approaches. This article provides a review of existing information systems, the main activities of scientific and educational organizations, ways of interaction with state and commercial enterprises. The analysis of general types of administrative and economic, financial activity, as well as scientific, educational, publishing activities, specialized for academic institutions is given. It is considered domestic, works dedicated to automation of processes and the introduction of information systems in scientific and educational organizations, as well as existing foreign technologies for automating the learning process. Most existing Russian and foreign systems include modules that provide electronic document management and communication. Despite existing standards, scientific and educational organizations are difficult to unify, due to their specialization and historically established traditions. Due to the multifaceted activity of scientific and educational organizations, individual proprietary software modules were created for the most demanded processes, which led to the problem of integrating modules developed at different times for different services accumulating databases with duplicate information. Information is provided on the corporate information systems developed in SPIIRAS, distinguished by the use of biometric contactless means of interaction with users and personalized maintenance scenarios.